ETHNIC HISTORY OF WEST (ANCIENT) ASIA, SOUTH AND SOUTHEAST ASIA, CENTRAL AND EAST ASIA. ETHNOGENESIS AND ETHNIC HISTORY, LANGUAGE AND RACE, ECONOMIC AND SOCIAL SYSTEM, MATERIAL AND SPIRITUAL CULTURE - Obidov Firdavs; Muzaffarova Dildora (PEDAGOGS, 2024)
Abstract: Each discipline differs from other disciplines by its research subject and methods. Ethnology has been studying the ethnic structure of peoples and the culture formed along with it since its emergence as a science. At the same time, the formation of any field of science as a science is closely related to the needs of people In this article, we will see how important science is in the study of the ethnology of Asian peoples In this article, we will get acquainted with the geographical division of Asian peoples and their ethnology. The population of each region is briefly described in the article.